2008
DOI: 10.1088/0957-4484/19/17/175302
|View full text |Cite
|
Sign up to set email alerts
|

Creation of damage-free ferroelectric nanostructures via focused ion beam milling

Abstract: We present a novel method for creating damage-free ferroelectric nanostructures with a focused ion beam milling machine. Using a standard e-beam photoresist followed by a dilute acid wash, nanostructures ranging in size from 1 µm down to 250 nm were created in a 90 nm thick lead zirconate titanate (PZT) wafer. Transmission electron microscopy and piezoresponse force microscopy (PFM) confirmed that the surfaces of the nanostructures remained damage free during fabrication, and showed no gallium implantation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Our initial investigations showed that the first problem could be addressed by utilizing a sacrificial Al layer on top of the BFO during 30keV direct FIB subtractive patterning to define nanoislands. Etched material that was re-deposited on top of the islands during definition was easily removed afterwards by chemical etching of the Al layer [16]. The second problem was tackled by utilizing lower ion beam energies; modern FIB ion columns can operate in the range from 30keV down to 5keV (or even as low as 2keV).…”
Section: Resultsmentioning
confidence: 99%
“…Our initial investigations showed that the first problem could be addressed by utilizing a sacrificial Al layer on top of the BFO during 30keV direct FIB subtractive patterning to define nanoislands. Etched material that was re-deposited on top of the islands during definition was easily removed afterwards by chemical etching of the Al layer [16]. The second problem was tackled by utilizing lower ion beam energies; modern FIB ion columns can operate in the range from 30keV down to 5keV (or even as low as 2keV).…”
Section: Resultsmentioning
confidence: 99%
“…Its influence on the functional properties extends to about 1 μm away from the milled grooves, therefore inhibiting any ferroelectricity in structures with lateral size <2 μm. For this reason, as performed also by other groups on different ferroelectric materials processed by FIB [20,27,32], thermal treatment procedures were considered in order to desorb the implanted ions and recrystallize the amorphized material.…”
Section: Direct Millingmentioning
confidence: 99%
“…A different approach for PZT was suggested by Hambe et al [27], namely, using a protective layer of photoresist during milling, to be removed by chemical etching. The resulting structures possessed ferroelectric properties up to the edges, still experiencing a 10-20 nm damaged layer at the sidewalls.…”
Section: Introductionmentioning
confidence: 99%
“…20 21 FIB has its strength in one-step maskless simpler, more flexible, and better-controlled nano-precision machining, patterning and fabrication especially for various submicron or nanoscale functional samples or devices via ion beam induced milling, etching and deposition due to its advantages of large depth of focus, high resolution, patterning flexibility, and direct-writing capability. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] In addition, another advantage of FIB is that it can be conveniently used to machine the biology to analyze its nanophotonic structures, 35 and FIB nanopatterning can be further used to fabricate the designed nanoscale devices inspired by the observed biophotonic structures. So far, although FIB has been widely used for nanopatterning and nanofabrication for some nanodevices/nanostructures, only a few literatures regarding FIB nanopatterning on the metallically-coated flat-top fiber endfaces can be referred to, and these fiber endface nanostructures were actually fabricated on the cleaved coarse fiber tips, 1 16-18 i.e., the used fiber tip diameters were equal to the optical fiber diameters instead of the thinner tapered/angled fiber tips.…”
Section: Introductionmentioning
confidence: 99%